The role of auxin transporters in monocots development - Balzan, Sara; Johal, Gurmukh S.; Carraro, Nicola (Frontiers in Plant Science, 2014)
Auxin is a key regulator of plant growth and development, orchestrating cell division, elongation and differentiation, embryonic development, root and stem tropisms, apical dominance and transition to flowering. Auxin levels are higher in undifferentiated cell populations and decrease following organ initiation and tissue differentiation. This differential auxin distribution is achieved by polar auxin transport (PAT) mediated by auxin transport proteins. There are 4 major families of auxin transporters in plants: PINs, ABCBs, AUX/LAXs and PILS. These families include proteins located at the plasma membrane (PM) or at the Endoplasmic Reticulum (ER), which participate in auxin influx, efflux or both, from the apoplast into the cell or from the cytosol into the ER compartment. Auxin transporters have been largely studied in the dicotyledon model species Arabidopsis, but there is increasing evidence of their role in auxin regulated development in monocotyledon species. In monocots, families of auxin transporters are enlarged and often include duplicated genes and proteins with high sequence similarity. Some of these proteins underwent sub- and neo-functionalization with substantial modification to their structure and expression in organs such as adventitious roots, panicles, tassels and ears. Most of the present information on monocot auxin transporters function derives from studies conducted in rice, maize, sorghum and Brachypodium using pharmacological applications (PAT inhibitors) or down-/up-regulation (over-expression and RNAi) of candidate genes. Gene expression studies and comparison of predicted protein structures have also increased our knowledge of the role of PAT in monocots. However, knockout mutants and functional characterization of single genes are still scarce and the future availability of such resources will prove crucial to elucidate the role of auxin transporters in monocot development.